The Role of Corporate Governance and Asymmetry Information in The Relationship Between Big Bath (large and non-recurring charges) and Audit Fees : An Overview Literature To Study Empirical - Sri Utami Nurhasanah; Sarah Fitriyani (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review explores the role of corporate governance and information asymmetry in the relationship between big bath accounting practices and audit fees. The findings suggest that firms engaging in big bath practices face higher audit fees due to increased audit risk perceived by auditors. Weak corporate governance exacerbates this effect, as auditors need to conduct more in-depth examinations to mitigate the associated risks. In addition, high information asymmetry between management and external stakeholders further increases audit risk, prompting auditors to expand their efforts. This study emphasizes the importance of strong corporate governance in reducing incentives for earnings management and enhancing financial transparency. The implications are significant for audit practice and corporate policy, highlighting the need for firms to strengthen their governance structures and for auditors to consider big bath risk in planning and conducting audits